Proficiency Test In Using Mail Merge feature of Microsoft Office With Expert System Algorithms - Devi Setiyoningrum; Anis Cherid (Jurnal Teknik Informatika C.I.T Medicom, 2018)
Manufacture of bulk mail is a common thing to do, both in the rural environment, academic, organization, or in layman's instansi.Selama administrative activities related to the mass mailing is done by creating a letter to then reproduced and edited manually one by one on different parts, for example on the part of the name and address. In fact, Microsoft Office has provided tools mail merge to create mass mailings that can handle multiple recipients with just one surat.Salah one solution to overcome this problem, many outstanding tutorials, discuss thoroughly the mail merge, but there needs to be a media that serves to test the extent to which knowledge of a person in control of such knowledge.. Expert systems is a system that is trying to adopt human knowledge into a computer so that the computer can resolve the issue as was done by experts, and expert systems are well designed in order to solve a particular problem by mimicking the work of the experts. Therefore, the need for application of expert systems that function to test proficiency in using the mail merge feature. The system is built using forward chaining and PHP programming language. need for an expert system application that serves to test proficiency in using the mail merge feature. The system is built using forward chaining and PHP programming language. need for an expert system application that serves to test proficiency in using the mail merge feature. The system is built using forward chaining and PHP programming language.